"The Pleasure Dome" : Amerikansk Experimentfilm 1939-1979. (Stockholm : Moderna museet, 1980)
Anger, Kenneth ; Baillie, Bruce ; Brakhage, Stan ; Breer, Robert ; Broughton, James ; Conner, Bruce ; Conrad, Tony ; Cornell, Joseph ; Fisher, Morgan ; Frampton, Hollis ; Gehr, Ernie ; Gerson, Barry ; etc.
"The Pleasure Dome": Amerikansk Experimentfilm 1939-1979 / American Experimental Film 1939-1979, Moderna Museet, Stockholm, 16 februari - 4 april 1980
kunstcatalogus
Keywords: Amerika